Factors Affecting Failure of Rural Entrepreneurs: Special Reference to Teldeniya Divisional Secretariat Area in Kandy District, Sri Lanka - G. A. T. R. Perera; Somasiri, J.K.S.P; S. M. C. Madhuwanthi (Kelaniya Journal of Management)
This study aims at identifying factors affecting to failure of rural entrepreneurs and to examine moderate impact of financial literacy over the failure of rural entrepreneurs. This quantitative study investigates rural entrepreneurial failure in Sri Lanka's Teldeniya Divisional Secretarial Area. A sample of 187 entrepreneurs, who experienced failure, was surveyed, focusing on factors like risk aversion, perseverance, and financial literacy as a moderating influence. Objectives included identifying failure contributors and examining financial literacy's moderating impact on rural entrepreneurship. The study highlights key competencies and their relationship with failure, emphasizing financial literacy's role. It contributes valuable insights for governments, development organizations, and rural entrepreneurs to address failure causes and leverage financial literacy for improved outcomes. The findings hold practical applications for enhancing rural entrepreneurship in Teldeniya and similar areas.